NANOSTRUCTURAL PROCESSES OF MELTING AND MOULDING OF THE EUTECTIC SILUMIN - V. Yu. Stetsenko (Литьë и металлургия)
It is shown that melting and molding of the eutectic silumin are difficult physical and chemical nanostructural processes. In them the major role is played by the centers of crystallization of the eutectic dendrites of aluminum, aluminum nanocrystals, the dissolved and adsorbed hydrogen. The role of the modifying gumboil is reduced to formation of a sodium emulsion. On it there is an allocation of vials of hydrogen at the eutectic crystallization. It promotes a branching of dendrites and receiving the modified silumin microstructure.